Memahami Motivasi Belajar Mahasiswa Dalam Memilih Jurusan Manajemen Universitas PGRI Semarang - Ahmad Qori’ul Hasan; Domas Yusuf Nur A.A; Rauly Sijabat (Educational Journal, 2026)
This study aims to explore students’ learning motivation in choosing the Management Study Program at Universitas PGRI Semarang. The research focuses on how students interpret the reasons, drives, and considerations behind their decision, particularly by examining the role of intrinsic and extrinsic motivation. This research employed a descriptive qualitative approach with one purposively selected informant. Data were collected through in-depth interviews and documentation, and then analyzed through data reduction, data display, and conclusion drawing/verification. The findings indicate that intrinsic motivation — including interest in business, the desire for self-development, and aspirations to run a personal business — is the most dominant factor influencing the decision to choose Management. Extrinsic motivation, such as parental support, peer influence, and promising career prospects, serves as a reinforcing element rather than the primary driver. Furthermore, practical and application-oriented learning experiences contribute to maintaining students’ learning motivation during their studies. These results suggest that choosing an academic major is not only based on practical considerations but is also closely related to students’ needs for self-actualization. This study is expected to provide useful insights for students, academic departments, and future researchers in understanding learning motivation within the context of major selection.